2018
DOI: 10.1371/journal.pone.0197204
|View full text |Cite
|
Sign up to set email alerts
|

Use of a platelet-rich plasma-collagen scaffold as a bioenhanced repair treatment for management of partial cruciate ligament rupture in dogs

Abstract: Dogs are commonly affected with cruciate ligament rupture (CR) and associated osteoarthritis (OA), and frequently develop a second contralateral CR. Platelet rich plasma (PRP) is a component of whole blood that contains numerous growth factors, which in combination with a collagen scaffold may act to promote bioenhanced primary repair of ligament. This study tested the hypothesis that treatment of partial stable CR stifles with an intra-articular collagen scaffold and PRP would decrease the disease progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
0
13
1
Order By: Relevance
“…It was shown that the level of transforming growth factor-β1 of both BMCs and MSCs group was significantly increased when compared with the saline group. In contrast to the findings of the present study, the tensile strength in the BMC group was restored to a near-normal level, whereas a recent 12-month follow-up study on the regeneration of canine partial cranial cruciate ligament tear treated with single intra-articular application of PRP-collagen demonstrated a high likelihood ratio of 19.5 ( P ​= ​0.0015) for progressing to a complete tear within 12-months of diagnosis [ 28 ]. Clinical studies regarding the bioenhanced regeneration of ACL partial tear was also divergent [ 29 ].…”
Section: Discussioncontrasting
confidence: 99%
“…It was shown that the level of transforming growth factor-β1 of both BMCs and MSCs group was significantly increased when compared with the saline group. In contrast to the findings of the present study, the tensile strength in the BMC group was restored to a near-normal level, whereas a recent 12-month follow-up study on the regeneration of canine partial cranial cruciate ligament tear treated with single intra-articular application of PRP-collagen demonstrated a high likelihood ratio of 19.5 ( P ​= ​0.0015) for progressing to a complete tear within 12-months of diagnosis [ 28 ]. Clinical studies regarding the bioenhanced regeneration of ACL partial tear was also divergent [ 29 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Early diagnosis is potentially useful for a precision medicine approach to patient management. For example, tibial plateau levelling osteotomy (TPLO) or regenerative medicine treatment for partial CR may be associated with improved functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, multiple effects of PRP have been documented in vivo and in vitro in human and veterinary medicine. In dogs, clinical studies are focused on orthopedics uses [35][36][37][38][39] and in dermatology for the treatment of wounds [40] or skin ulcers with extensive tissue loss [41][42][43], chronic ulcers [44], surgically induced wounds [45][46][47][48], alopecia [49] and for antimicrobial effects in infected skin wounds [50]. The results of these studies have been variable which may reflect the lack of standardization of the methods for obtaining the PRP.…”
Section: Of 16mentioning
confidence: 99%